NEUROINTERVENSI PENATALAKSANAAN STROKE ISKEMIK FASE AKUT TERKINI ULASAN SINGKAT STUDI MR CLEAN ESCAPE EXTENDIA DAN SWIFT PRIME - Fritz Sumantri Usman* (Neurona Majalah Kedokteran Neuro Sains, 2016)
DEVELOPMENT OF THERAPEUTIC MANAGEMENT OF ACUTE ISCHEMIC STROKE IS DYNAMIC AND IMPROVING SEVERAL LARGE STUDIES SUCH AS MR CLEAN ESCAPE EXTEND IA AND SWIFT PRIME SHOWED A HIGHLY SIGNIFICANT IMPROVEMENT RESULTS IN THE ACUTE PHASE OF ISCHEMIC STROKE THESE STUDIES COMBINED TWO METHODS OF THROMBOLYSIS INTRAARTERIAL OR INTRAVENOUS FOLLOWED BY THROMBECTOMY